Effects of water temperature increase and heavy metals contamination on WAP65 gene expression in sea bass (Dicentrarchus labrax) liver - Pierre, S.; Tarnowska, K.; Hachfi, L.; Coupé, S.; Simide, R.; Couvray, S.; Garnier, C.; Grimaldi, M.; Richard, S.; Gaillard, S.; Prévot-d'alvise, N.; Grillasca, J. P. (Cellular and Molecular Biology, 2011)
It has been previously demonstrated that "Warm temperature Acclimation-related 65kD Protein” (WAP65) is involved in temperature acclimation, response to intoxication and infection, as well as in development. The expression of wap65-1 was investigated in the liver of European sea bass (Dicentrarchus labrax) during exposure to the increased temperature (from 12 °C to 30 °C) and during intoxication with four heavy metals: lead, cadmium, copper and zinc. Post temperature increase wap65 expression was highest after one hour at 30 °C. After 1 to 4 weeks at 30 °C wap65 transcript levels did not differ from the 12°C control group, similar to observations regarding the heat shock protein, hsp70. Upregulation of wap65 was detected after treatment (intoxication) with cadmium (0.5 Î¼g/l). In contrast, a slight, but significant down regulation of wap65 was seen after copper (5 Î¼g/l) intoxication. These data indicate that functional analyses of WAP65 are needed to understand the differential regulation of this gene by metals. The role of WAP65 may be similar to that of HSP70, which has generalized functions in responding to certain stressors and maintaining normal cell physiology.